Impact of COVID-19 public health restrictions on older people in Uganda: “hunger is really one of those problems brought by this COVID” - Clarissa, Giebel; Bwire, Ivan; Philomena, Burger; Isaac, Ddumba (Cambridge University Press, 2020)
ABSTRACT Objectives: To explore the impact of COVID-19 public health restrictions on the lives of older adults living in Uganda. Design: Qualitative semi-structured interview study. Setting: Participants’ homes. Participants: Older adults living in Uganda (aged 60+). Measurements: Older adults in Uganda were interviewed over the phone and asked about their lives before and since COVID-19, and how public health restrictions have affected their lives. Semi-structured interviews were audio-recorded, transcribed and translated into English. Transcripts were thematically analyzed and themes generated in discussion. Results: In total, 30 older adults participated in the study. Five themes were identified: (1) economic impacts; (2) lack of access to basic necessities; (3) impact on healthcare utilization; (4) social impacts and (5) violent reinforcement of public health restrictions. COVID-19 public health restrictions had severe impacts on their lives, with many people having not enough food to eat due to lack of income, and being unable to pay their grandchildren’s school fees. Steep rises in public transport fares and an overall avoidance of transport also resulted in a lack of access to healthcare services and difficulty in getting food. Restrictions were violently reinforced by security guards. Conclusions: Public health restrictions have a severe impact not only on older adults but also on the whole family in Uganda. Governmental strategies to contain the virus need to provide more support to enable people to get basic necessities and live as normal a life as possible.
Keywords: Ageing ,COVID-19, Developing countries, public health